Omaezallene from Red Alga Laurencia sp.: Structure Elucidation, Total Synthesis, and Antifouling Activity - Umezawa, Taiki; Oguri, Yuko; Matsuura, Hiroshi; Yamazaki, Shohei; Suzuki, Masahiro; Yoshimura, Erina; Furuta, Takeshi; Nogata, Yasuyuki; Serisawa, Yukihiko; Matsuyama-Serisawa, Kazuyo; Abe, Tsuyoshi; Matsuda, Fuyuhiko; et al. (Angewandte Chemie International Edition, 2014)
Natural antifouling products have been the subject of considerable attention. We screened marine algae for antifouling activity and discovered omaezallenes, the new bromoallene‐containing natural products isolated from the red alga Laurencia sp. Described is the isolation, structure elucidation, and total syntheses of omaezallenes. The relative and absolute configurations of natural omaezallenes were unambiguously established through total synthesis. The antifouling activities and ecotoxicity of omaezallenes were also evaluated. Omaezallene, a new brominated antifouling natural product isolated from the red alga Laurencia sp., was synthesized and its structure elucidated through NMR experiments. The antifouling activities of omaezallene and its isomers against the cypris larvae of the barnacle Amphibalanus amphitrite were also evaluated.